An optical/electronic artificial skin extends the robotic sense to molecular sensing - Benhui Dai; Yingjie Zheng; Yihang Qian; Xiaoyong Hu; Zhizhong Sun; Zenghong Ma; Guanjun Bao; Huaping Wu; Xuan Luo; Josie Hughes; Xiangjiang Liu; Yibin Ying; et al. (npj Flexible Electronics)
Abstract Artificial skins are essential for bridging sensory gaps between robots and environments, enabling natural and intuitive interactions. While artificial skins can sense stimuli like pressure and stretchability, their capabilities need to be expanded into chemical sensing for specific applications. Here, we introduce optical/electronic artificial skins (oe-skins), advancing robotic sensing from physical perception to chemical sensation. Our design integrates optical fibers into a carbon nanotube (CNT)-based haptic electronic skin. This empowers the skin to sense force and temperature, while detecting near-infrared (NIR) optical signals from molecules, giving dual modalities of physical and chemical sensing. We successfully implement the oe-skin into robots, enabling intraocular pressure and glucose level detection for diagnosing glaucoma and diabetes. Additionally, we demonstrated their effectiveness in delicately harvesting fruits and grading them by ripeness, firmness, and sugar levels. We present a blueprint for next-generation intelligent electronics where technological progress aligns with sustainable development and societal well-being.